2022
DOI: 10.1177/00219096221123739
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Climate-Smart Adaptation Strategies: Farm-Level Evidence from India

Abstract: The paper attempts to examine the factors that influence climate-smart adaptation (CSA) strategies. The study used binary logit and multivariate probit models to understand the dynamics and factors of agricultural households’ behavioural decisions on CSA strategies. Based on the results of the binary logit model, the study indicated that factors such as access to extension services and training, gender, educational level, land ownership, access to irrigation, access to credit and crop damage level positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Farmers with higher education levels were more likely to choose measures related to recommended adaptation measures such as improved fertilizer application and soil management methods, while those with a lower level of education were more likely to choose measures related to indigenous farming methods and embankment building practices. Sahoo and Moharaj (2022) found that the educated households were more likely to adopt the climate change adaptation strategies than those less educated. Moreover, in a similar study, Do and Ho (2022) found that education of farm households and farmer’s belief in climate change are the major factors prompting farm households to adopt climate change adaptation strategies in the Mekong Delta of Vietnam.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Farmers with higher education levels were more likely to choose measures related to recommended adaptation measures such as improved fertilizer application and soil management methods, while those with a lower level of education were more likely to choose measures related to indigenous farming methods and embankment building practices. Sahoo and Moharaj (2022) found that the educated households were more likely to adopt the climate change adaptation strategies than those less educated. Moreover, in a similar study, Do and Ho (2022) found that education of farm households and farmer’s belief in climate change are the major factors prompting farm households to adopt climate change adaptation strategies in the Mekong Delta of Vietnam.…”
Section: Resultsmentioning
confidence: 95%
“…It also determines the level of risk being exposed, the vulnerability of a system or community and socioeconomic development (Deressa et al , 2009; Tun Oo, 2018; IPCC, 2022). There are increasing assessments on the adaptation actions to understand and estimate the magnitude and rate of climate change and associated risks (Tun Oo et al , 2017; Sahoo and Moharaj, 2022; Nguyen and Bleys, 2023; Gemeda et al , 2023). Despite the progress achieved, however, adaptation gaps are still present between current levels of adaptation and levels needed to respond to reduce the climate risks.…”
Section: Introductionmentioning
confidence: 99%
“…The division of greenhouse gas (GHG) mitigation responsibilities between developed and developing nations underscores the urgent need for adaptive strategies that bolster ecosystem resilience to the impacts of climate change (Vincent and Cull 2010). This imperative has catalyzed an increase in vulnerability assessment research across various scales, including local (T N Balasubramanian et al 2007), national (Moss et al 2001;Vincent 2004), zonal (Heltberg and Bonch-Osmolovskiy 2011), provincial/state (Brenkert and Malone 2005), district (Nadeem et al 2022;Bahinipati 2014;TERI 2003;O'Brien et al 2004;Palanisami et al 2009;Patnaik and Narayan 2005;Palanisami et al 2010), community (Balasubramanium et al 2009Young et al 2010), and household levels (Sahoo and Moharaj 2022;Deressa et al 2008;Hahn et al 2009). These studies provide essential insights that enable policymakers to allocate limited resources effectively in the development and implementation of adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…These are important ways to bring small farmers out of the poverty trap and to stimulate youth's interest in agriculture (Swaminathan, 2016). Even though various measures have been taken to make farming more profitable and to protect the farmers from unwanted economic distress, the persistence of agrarian catastrophes has contributed to the extensive occurrence of farmer suicides in India (Sahoo and Moharaj, 2022).…”
Section: Introductionmentioning
confidence: 99%